Association of blood pressure with cardiovascular outcome and mortality: results from the KNOW-CKD study. Issue 9 (2nd September 2021) - Lee, Jee Young; Park, Jung Tak; Joo, Young Su; Lee, Changhyun; Yun, Hae-Ryong; Chang, Tae Ik; Kim, Yeong-Hoon; Chung, WooKyung; Yoo, Tae-Hyun; Kang, Shin-Wook; Park, Sue K; Chae, Dong Wan; et al.
Abstract: Background: Optimal blood pressure (BP) control is a major therapeutic strategy to reduce adverse cardiovascular events (CVEs) and mortality in patients with chronic kidney disease (CKD). We studied the association of BP with adverse cardiovascular outcome and all-cause death in patients with CKD. Methods: Among 2238 participants from the KoreaN cohort study for Outcome in patients With CKD (KNOW-CKD), 2226 patients with baseline BP measurements were enrolled. The main predictor was systolic BP (SBP) categorized by five levels: <110, 110–119, 120–129, 130–139 and ≥140 mmHg. The primary endpoint was a composite outcome of all-cause death or incident CVEs. We primarily used marginal structural models (MSMs) using averaged and the most recent time-updated SBPs. Results: During the follow-up of 10 233.79 person-years (median 4.60 years), the primary composite outcome occurred in 240 (10.8%) participants, with a corresponding incidence rate of 23.5 [95% confidence interval (CI) 20.7–26.6]/1000 patient-years. MSMs with averaged SBP showed a U-shaped relationship with the primary outcome. Compared with time-updated SBP of 110–119 mmHg, hazard ratios (95% CI) for <110, 120–129, 130–139 and ≥140 mmHg were 2.47 (1.48–4.11), 1.29 (0.80–2.08), 2.15 (1.26–3.69) and 2.19 (1.19–4.01), respectively. MSMs with the most recent SBP also showed similar findings. Conclusions: In Korean patients with CKD, there was a U-shaped association of SBP with the risk of adverse clinical outcomes. Our findings highlight the importance of BP control and suggest a potential hazard of SBP <110 mmHg.